2015
DOI: 10.1016/j.nut.2014.06.007
|View full text |Cite
|
Sign up to set email alerts
|

Dietary patterns among 13-y-old Portuguese adolescents

Abstract: Unhealthier behaviors and lower socioeconomic position were the main factors associated with the unhealthier dietary pattern (fast food and sweets). This information should be considered in the development of health-promotion interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
37
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(50 citation statements)
references
References 35 publications
5
37
0
8
Order By: Relevance
“…On the contrary, unhealthy dietary behavioural practices such as a high frequency of breakfast skipping, and high frequency of eating-out from home in a week, and intakes of fast foods, carbonated sweetened beverages and snacking in a day were significantly and positively associated with greater adherence to the "western-based" food pattern among these adolescents. These findings are consistent with several studies of adolescents of comparable age from other countries [9,11,22,26]. In a study of Korean adolescents, those with high intakes of bread, noodles, cookies and pizza/hamburgers were more likely to consume more fast foods, fried foods and carbonated beverages as well as having a high frequency of eating-out from home [11].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…On the contrary, unhealthy dietary behavioural practices such as a high frequency of breakfast skipping, and high frequency of eating-out from home in a week, and intakes of fast foods, carbonated sweetened beverages and snacking in a day were significantly and positively associated with greater adherence to the "western-based" food pattern among these adolescents. These findings are consistent with several studies of adolescents of comparable age from other countries [9,11,22,26]. In a study of Korean adolescents, those with high intakes of bread, noodles, cookies and pizza/hamburgers were more likely to consume more fast foods, fried foods and carbonated beverages as well as having a high frequency of eating-out from home [11].…”
Section: Discussionsupporting
confidence: 90%
“…Food consumption patterns are also influenced by a multitude of factors such as sociodemographic status, dietary behaviours and lifestyle practices [6,7]. Few studies that have examined the association between all these factors on food patterns among children and adolescents and they tend to report that a healthy food pattern, characterised by high intake of fruit, vegetables, and dairy products, is positively associated with higher socio-economic status (SES) and educational status [6][7][8], and was inversely associated with unhealthy lifestyle behaviours such as smoking, excessive alcohol consumption and low physical activity [6][7][8][9]. Most of these studies were carried-out with Caucasian children and adolescents, with only a few dealing with Asian children [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…We identified a few studies that have also assessed DP during adolescence and associated factors [13,29,30]. An English longitudinal study assessed a priori DP among children and adolescents followed up from age 7 to 15 years, reporting that an energy-dense, high-fat, lowfiber DP was prospectively associated with greater levels of adiposity [30].…”
Section: Discussionmentioning
confidence: 99%
“…Consistently, a study carried out by Oellingrath et al [31] with Norwegian pre-teens and adolescents identified four DPs using PCA (snacks, convenient, varied Norwegian, and dieting), reporting greater adherence to "Dieting" DP among girls. Additionally, in a study including Portuguese adolescents aged 13 years, 40% of them adhered to a dietary pattern named "low intake", which was associated with higher proportion of overweight/obese [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation